3(x+2)-2=6(x+1)-3x

Simple and best practice solution for 3(x+2)-2=6(x+1)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-2=6(x+1)-3x equation:


Simplifying
3(x + 2) + -2 = 6(x + 1) + -3x

Reorder the terms:
3(2 + x) + -2 = 6(x + 1) + -3x
(2 * 3 + x * 3) + -2 = 6(x + 1) + -3x
(6 + 3x) + -2 = 6(x + 1) + -3x

Reorder the terms:
6 + -2 + 3x = 6(x + 1) + -3x

Combine like terms: 6 + -2 = 4
4 + 3x = 6(x + 1) + -3x

Reorder the terms:
4 + 3x = 6(1 + x) + -3x
4 + 3x = (1 * 6 + x * 6) + -3x
4 + 3x = (6 + 6x) + -3x

Combine like terms: 6x + -3x = 3x
4 + 3x = 6 + 3x

Add '-3x' to each side of the equation.
4 + 3x + -3x = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
4 + 0 = 6 + 3x + -3x
4 = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
4 = 6 + 0
4 = 6

Solving
4 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4y-8-27=2-(-2) | | 14x-79=8x-25 | | 4x-(x+3)=6 | | -10+5y-35=-4 | | -10+5-35=-4 | | 7a-b=15 | | 175=85+(15+8)w | | (x-78)+x=180 | | 3b-12=6b-8 | | m+1=-1+3m | | -4y+36=4(3y-3) | | 5x-1x=15 | | 3.4x+5=22 | | 2.5x+2.5=12.5 | | 2.1(a+0.5)=-2.1(a+20) | | -5t-7t=2t | | -5x-24=2x+11 | | 5(c-1)-2(c+3)-2c=-8 | | 23=-3m+2 | | 11-4z=-27 | | 4y-14=6y-16 | | -5t-7t= | | -8x+4=3x+4 | | (x+16)+(7x-20)=180 | | .5x+4=.66x+.5 | | -3a+16=-20 | | 3x^2+27x-6= | | 8(2n+3)=9(4n+4)+2 | | -(6y+1)-(-5y-7)=-2 | | 17a-8=54-6y | | 4(2(10.5)+1)-3(2(10.5)-5)=40 | | 3t-66=899 |

Equations solver categories